Unsteady Mixed Convection Boundary Layer from a Circular Cylinder in a Micropolar Fluid - Anati Ali; Norsarahaida Amin; Ioan Pop (International Journal of Chemical Engineering)
Most industrial fluids such as polymers, liquid crystals, and colloids contain suspensions of rigid particles that undergo rotation. However, the classical Navier-Stokes theory normally associated with Newtonian fluids is inadequate to describe such fluids as it does not take into account the effects of these microstructures. In this paper, the unsteady mixed convection boundary layer flow of a micropolar fluid past an isothermal horizontal circular cylinder is numerically studied, where the unsteadiness is due to an impulsive motion of the free stream. Both the assisting (heated cylinder) and opposing cases (cooled cylinder) are considered. Thus, both small and large time solutions as well as the occurrence of flow separation, followed by the flow reversal are studied. The flow along the entire surface of a cylinder is solved numerically using the Keller-box scheme. The obtained results are compared with the ones from the open literature, and it is shown that the agreement is very good.